The Term Which is Contrary to the Requirements of the Substance (Nature) of Contract - Reza Maqsūdi; Sayyid Mustafa Mohaqqiq Damad; Sayyid Mahdi Allameh; Ali Reza Mazlūm Rahni; Hormoz Asadi Koohbad (آموزه‌‌های فقه مدني)
The compatibility with the requirements of the contract, according to clause 1 of Article 233 of the Civil Code, is one of the special conditions of the correctness (validity) of the condition. However, it is silent about the basis of the nullity of the repugnant condition and it is also, silent about what the criterion is in determining and distinguishing the requirements of the substance from the absoluteness. Therefore, the mentioned ruling (judgment) is not comprehensive and clear and is insufficient. This shortcoming and obscurity have caused a difference of opinion among civil rights authors. First of all, the authors by descriptive-analytical method enumerate and explain the theoretical foundations of the aforementioned ruling, including rational proof and narrative proof in jurisprudential works, and then, selects the theory of the elements of contracts among the interpretations available in the criterion of distinguishing the necessity of the substance (essence, nature) from the application. Therefore, any condition which is contrary to one of the general or specific elements of the contract, because of the contradiction within that condition in relation to that contract, is an obstacle to the realization of the contract and against the requirements of the nature of the contract.